Maize orthologs of rice GS5 and their trans‐regulator are associated with kernel development. Issue 11 (26th September 2015) - Liu, Jie; Deng, Min; Guo, Huan; Raihan, Sharif; Luo, Jingyun; Xu, Yuancheng; Dong, Xiaofei; Yan, Jianbing
Abstract: Genome information from model species such as rice can assist in the cloning of genes in a complex genome, such as maize. Here, we identified a maize ortholog of rice GS5 that contributes to kernel development in maize. The genome‐wide association analysis of the expression levels of ZmGS5, and 15 of its 26 paralogs, identified a trans ‐regulator on chromosome 7, which was a BAK1 ‐like gene. This gene that we named as ZmBAK1‐7 could regulate the expression of ZmGS5 and three of the paralogs. Candidate‐gene association analyses revealed that these five genes were associated with maize kernel development‐related traits. Linkage analyses also detected that ZmGS5 and ZmBAK1‐7 co‐localized with mapped QTLs. A transgenic analysis of ZmGS5 in Arabidopsis thaliana L. showed a significant increase in seed weight and cell number, suggesting that ZmGS5 may have a conserved function among different plant species that affects seed development. Abstract : ZmGS5 and ZmBAK1‐7 were associated with maize kernel development‐related traits in association mapping population and also co‐localized with mapped QTLs in this study. ZmBAK1‐7 could regulate the expression of ZmGS5 . A transgenic analysis of ZmGS5 in Arabidopsis showed a significant increase in seed weight and cell number.